Tingkat Inteligensi Siswa dengan Kesulitan Membaca, Menulis, dan Berhitung di Kota Makassar - Agussalim, Amirah Aminanty (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. This study aims to describe the intelligence levels of elementary school students experiencing difficulties in reading, writing, and arithmetic in Makassar City. The research employed a quantitative approach with a descriptive analysis method. The subjects were 64 students from eight elementary schools who their teachers identified as having learning difficulties. The Coloured Progressive Matrices (CPM) test was used to measure the students' intelligence levels. The results showed that most students with difficulties in reading, writing, and arithmetic had intelligence levels in the average category. Furthermore, the majority of identified students were male, and learning difficulties were most prevalent among students in the third and fourth grades. These findings confirm that most participants in this study did not have low intelligence, but rather specific cognitive process disorders. Further comprehensive assessment is recommended to obtain a more complete picture of the learning difficulties experienced. This study also highlights the importance of early detection and appropriate intervention for students with learning difficulties, enabling them to develop optimally. Keywords: Intelligence level, learning difficulties, elementary school